2013
DOI: 10.1038/hdy.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding geographic origins and history of admixture among chimpanzees in European zoos, with implications for future breeding programmes

Abstract: Despite ample focus on this endangered species, conservation planning for chimpanzees residing outside Africa has proven a challenge because of the lack of ancestry information. Here, we analysed the largest number of chimpanzee samples to date, examining microsatellites in 4100 chimpanzees from the range of the species in Africa, and 20% of the European zoo population. We applied the knowledge about subspecies differentiation throughout equatorial Africa to assign origin to chimpanzees in the largest conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…In the Taï Forest (Côte D’Ivoire), female chimpanzees mated more with those males who shared meat with them than with those who did not (Gomes and Boesch 2009, 2011); in Guinea, male chimpanzees were more likely to engage successfully in consortship with cycling females with whom they shared fruits more frequently (Hockings et al 2007). Similarly in captive chimpanzees, often fully or partially of West African descent (Ely et al 2005; Hvilsom et al 2013), female chimpanzees mated more frequently with males that groomed them more (Hemelrijk et al 1992), whilst the market forces of supply and demand influenced the amount of grooming that males directed to cycling females: males groomed females showing sexual swellings more when the availability of such females decreased (Koyama et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In the Taï Forest (Côte D’Ivoire), female chimpanzees mated more with those males who shared meat with them than with those who did not (Gomes and Boesch 2009, 2011); in Guinea, male chimpanzees were more likely to engage successfully in consortship with cycling females with whom they shared fruits more frequently (Hockings et al 2007). Similarly in captive chimpanzees, often fully or partially of West African descent (Ely et al 2005; Hvilsom et al 2013), female chimpanzees mated more frequently with males that groomed them more (Hemelrijk et al 1992), whilst the market forces of supply and demand influenced the amount of grooming that males directed to cycling females: males groomed females showing sexual swellings more when the availability of such females decreased (Koyama et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A recent research on the genetic characterization of captive chimpanzees in Europe using 30 polymorphic microsatellite markers revealed that 40% of genotyped individuals were of western African origin, 18% of central Africa origin, 5% of eastern African origin and 23% hybrids (Hvilsom et al 2013). A limitation of our study derives from the use of a single mitochondrial marker instead of nuclear polymorphic markers, which affects the accuracy of our subspecies classification.…”
Section: Discussionmentioning
confidence: 87%
“…Given the current situation of the populations of chimpanzees held in captivity, it is desirable to develop an identification plan involving Latin American zoological institutions. Zoos and primate rehabilitation centers could play a major role in the reception and subsequent reintroduction of animals, through development of studbooks for captive chimpanzees to minimize inbreeding and to preserve maximum genetic diversity (Carlsen 2009;Hvilsom et al 2013). It should be noted that the release of captive chimpanzees in wild areas could be carried out successfully, representing a potential benefit to the conservation of this species (Goossens et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of anthropogenic hybridization in captivity can be either intentional, when i) populations that have been through severe bottlenecks can benefit from gene introgression to tackle inbreeding depression [13], ii) fertile individuals of only one sex remain, both in the wild and in captivity [14], or iii) the sexual rate is unbalanced, and individuals of the exceeding sex are crossed with a related species to maintain sexual libido while individuals of its own species are not available (present study), or unintentional, when i) founders are obtained or confiscated from animal keepers that have permitted or stimulated hybridizations [10], ii) cryptic species are kept in the same breeding facilities [9, 11, 15], iii) taxonomically unresolved taxa are combined [16, 17], or iv) hybrids were already present in the wild populations that founded the captive program [16]. …”
Section: Introductionmentioning
confidence: 99%
“…In these cases, after a number of backcrosses, hybrids become morphologically indistinguishable from the parental species, making the conservation of a threatened taxa more difficult, and the use of molecular genetic markers is often the only way to assign admixture levels [9, 11, 12]. Despite the theoretically controlled captive conditions, recent genetic analyses have proven that unintentional gene introgressions have affected even some of the most traditional ex situ conservation programs, including the American Bison [10], Chimpanzees [11], and Tigers [9], suggesting that other programs might also be vulnerable to this problem, especially ones that are established in countries in which captive management is not regulated by official organizations.…”
Section: Introductionmentioning
confidence: 99%